국내 대학생의 마약 사용 실태 및 마약허용태도 요인에 대한 탐색적 연구 - 이세림(Serim Lee); 전종설(JongSerl Chun); 강민정(Minjeong Kang) (한국콘텐츠학회 논문지, 24(10), 2024)
국내 청년세대 마약 사용이 심각한 사회적 문제로 대두되고 있지만, 그 실태조차 정확히 파악되지 못하고 있는 상황이다. 이에 본 연구는 국내 대학생의 마약허용태도 및 마약 사용에 대해 탐색적으로 파악하고자 하였다. 계획행동이론, 건강신념모델에 기반하여, 본 연구는 마약에 대한 태도를 마약 사용에 영향을 미칠 수 있는 강력한 예측요인으로 보고, 마약허용태도에 미치는 다양한 위험요인을 분석하고자 했다. 이를 위해 국내 대학생 301명을 대상으로 설문조사를 진행하였다. 분석 결과, 2%가 마약을 사용해본 경험이 있는 것으로 나타났으며 마약허용태도 수준은 5점 만점에 1.64점으로 나타났다. 선형회귀분석 결과, 성별, 자기통제력, 사회적 낙인이 마약허용태도에 영향을 미치는 것으로 나타났다. 본 연구는 국내 대학생의 마약 사용 실태와 마약허용태도의 영향요인에 대한 통찰력을 제공한다는 점에서 의의가 있다. 나아가 연구결과를 토대로 향후 청년세대의 마약 사용 예방에 대해 논의하고 제언하였다. Drug use among Korean young adults is increasingly recognized as a significant societal concern, yet remains poorly understood. Therefore, this study aimed to comprehensively investigate the attitudes towards and usage of drugs among Korean college students. Drawing upon the Theory of Planned Behavior, and the Health Belief Model, this research considered drug attitudes as a key predictor of usage and examined various risk factors influencing drug permissive attitudes. A survey was administered to 301 college students in South Korea to achieve this. Results indicated that 2% reported drug use experiences, with drug permissive attitudes averaging 1.64 out of 5 points. Notably, linear regression analysis highlighted gender, self-control, and social stigma as significant influencers on drug permissive attitudes. This study sheds light on the realities of drug usage and determinants of drug permissive attitudes among Korean college students. Moreover, it offers discussions and recommendations for future interventions aimed at preventing drug use among young adults. KCI Citation Count: 0